Peningkatan Efikasi Diri Matematika melalui Metode Belajar Mind Map - Gita Aulia Nurani; Asmadi Alsa (Psympathic : Jurnal Ilmiah Psikologi, 2021)
This study aims to test empirically the effect of the mind maps visual learning method on increasing the self-efficacy of learning mathematics in junior high school students. The research design used a quasi-experimental design with the one-group pretest-posttest design. The research subjects were collected using a non-random purposive sampling technique with 22 students who had moderate to low self-efficacy scores. Data collection used the mathematics self-efficacy scale, and data analysis using repeated analysis of variance. The results showed that there was a difference in the average score of learning mathematics self-efficacy between pre-test and post-test. This finding may indicate that the mind maps visual learning method has a positive effect on increasing the self-efficacy of learning mathematics in junior high school students. The increase in the average self-efficacy score in the generalization dimension was 5.8 points, the level dimension was 4.5 points, and the strength dimension was 3.1 points.